The Governance and the Social Performance of Banks: Comparison between the Model Germano-Nippon and the Model Franco-Italian (Global Journal of Management and Business Research, 2016)
This article discusses the influence of internal mechanisms of governance on the social performance in the context germano-Nippon and in the context Franco-Italian. We are going to put the light on the model germano-Nippon and the model Franco-Italian, governance and the social performance. Then, we will analyze the effects that exercise internal governance mechanisms on the social performance of banks belong to the context germano-Nippon and the context Franco-Italian. In order to measure the social performance, we have retained the equality between the Man and the woman, the social climate, the transparency of information and the conditions of work and to apprehend the governance we retained the council of administration, its size, its independence and the concentration of capital.
Keywords: governance; social performance; the system germano-nippon; the system francoitalian